Tyrosine hydroxylase deficiency: a treatable disorder of brain catecholamine biosynthesis - Willemsen, Michèl A.; Verbeek, Marcel M.; Kamsteeg, Erik-Jan; Rijk-van Andel, Johanneke F. de; Aeby, Alec; Blau, Nenad; Burlina, Alberto; Donati, Maria A.; Geurtz, Ben; Grattan-Smith, Padraic J.; Haeussler, Martin; Hoffmann, Georg F.; et al. (Brain, 2010)
Tyrosine hydroxylase deficiency is an autosomal recessive disorder resulting from cerebral catecholamine deficiency. Tyrosine hydroxylase deficiency has been reported in fewer than 40 patients worldwide. To recapitulate all available evidence on clinical phenotypes and rational diagnostic and therapeutic approaches for this devastating, but treatable, neurometabolic disorder, we studied 36 patients with tyrosine hydroxylase deficiency and reviewed the literature. Based on the presenting neurological features, tyrosine hydroxylase deficiency can be divided in two phenotypes: an infantile onset, progressive, hypokinetic-rigid syndrome with dystonia (type A), and a complex encephalopathy with neonatal onset (type B). Decreased cerebrospinal fluid concentrations of homovanillic acid and 3-methoxy-4-hydroxyphenylethylene glycol, with normal 5-hydroxyindoleacetic acid cerebrospinal fluid concentrations, are the biochemical hallmark of tyrosine hydroxylase deficiency. The homovanillic acid concentrations and homovanillic acid/5-hydroxyindoleacetic acid ratio in cerebrospinal fluid correlate with the severity of the phenotype. Tyrosine hydroxylase deficiency is almost exclusively caused by missense mutations in the TH gene and its promoter region, suggesting that mutations with more deleterious effects on the protein are incompatible with life. Genotype-phenotype correlations do not exist for the common c.698G>A and c.707T>C mutations. Carriership of at least one promotor mutation, however, apparently predicts type A tyrosine hydroxylase deficiency. Most patients with tyrosine hydroxylase deficiency can be successfully treated with l-dopa.
Published: 29 April 2010
Gesehen am 07.02.2024